Optimizing Sentinel Surveillance to Target Containment of Emerging Multidrug-Resistant Organisms in Regional Networks. (October 2020) - Paul, Prabasaj; Slayton, Rachel; Kallen, Alexander; Walters, Maroya; Jernigan, John
Abstract : Background: Successful containment of regional outbreaks of emerging multidrug-resistant organisms (MDROs) relies on early outbreak detection. However, deploying regional containment is resource intensive; understanding the distribution of different types of outbreaks might aid in further classifying types of responses. Objective: We used a stochastic model of disease transmission in a region where healthcare facilities are linked by patient sharing to explore optimal strategies for early outbreak detection. Methods: We simulated the introduction and spread of Candida auris in a region using a lumped-parameter stochastic adaptation of a previously described deterministic model ( Clin Infect Dis 2019 Mar 28. doi:10.1093/cid/ciz248). Stochasticity was incorporated to capture early-stage behavior of outbreaks with greater accuracy than was possible with a deterministic model. The model includes the real patient sharing network among healthcare facilities in an exemplary US state, using hospital claims data and the minimum data set from the CMS for 2015. Disease progression rates for C. auris were estimated from surveillance data and the literature. Each simulated outbreak was initiated with an importation to a Dartmouth Atlas of Health Care hospital referral region. To estimate the potential burden, we quantified the "facility-time" period during which infectious patients presented a risk of subsequent transmission within each healthcare facility. Results: Of the 28, 000 simulated outbreaks initiated with an importation to the community, 2, 534 resulted in patients entering the healthcare facility network. Among those, 2, 480 (98%) initiated a short outbreak that died out or quickly attenuated within 2 years without additional intervention. In the simulations, if containment responses were initiated for each of those short outbreaks, facility time at risk decreased by only 3%. If containment responses were initiated for the 54 (2%) outbreaks lasting 2 years or longer, facility time at risk decreased by 79%. Sentinel surveillance through point-prevalence surveys (PPSs) at the 23 skilled-nursing facilities caring for ventilated patients (vSNF) in the network detected 50 (93%) of the 54 longer outbreaks (median, 235 days to detection). Quarterly PPSs at the 23 largest acute-care hospitals (ie, most discharges) detected 48 longer outbreaks (89%), but the time to detection was longer (median, 716 days to detection). Quarterly PPSs also identified 76 short-term outbreaks (in comparison to only 14 via vSNF PPS) that self-terminated without intervention. Conclusions: A vSNF-based sentinel surveillance system likely provides better information for guiding regional intervention for the containment of emerging MDROs than a similarly sized acute-care hospital–based system. Funding: None Disclosures: None